Pengaruh Promosi Digital dan Customer Experience Terhadap Keputusan Pembelian Pada Toko Baju Kafa Kids & Baby Shop Lombok Timur - Helsani; Weni Retnowati (Postgraduate, University of Mataram, 2025)
This study aims to determine whether digital promotion and customer experience affect purchasing decisions at the Kafa Kids & Baby Shop in East Lombok. The research method used is quantitative with an associative approach. The researcher collected data by distributing questionnaires to 100 respondents, with the aim of understanding the relationship between the variables studied. The data obtained were then analyzed using SPSS (Statistical Package for the Social Sciences) software. The analysis results show that digital promotion has a positive and significant effect on purchasing decisions, with a calculated t value of 3.118, which is greater than the table t value of 1.984. Customer experience also has a positive and significant effect on purchasing decisions, with a calculated t value of 8.145, greater than the table t value of 1.984. Thus, it can be concluded that both digital promotion and customer experience positively and significantly influence consumer purchasing decisions at Kafa Kids & Baby Shop in East Lombok.